Utilizacion de la coloracion giemsa cobalto en raspado de lesiones como ayuda de diagnostico de leshmaniasis, de los pacientes atendidos en el instituto izquieta perez de esmeraldas, en el periono comprendido octubre – diciembre del 2009 - Campo Morales, María Elena (2010)
The Leishmaniasis is a zoonotic disease caused by different species of protozoa gender Leishmania. This disease is transmitted by the bite of an insect díptero of gender lutzomya, Psychodidae, causing various forms of the disease, ranging from skin ulcers (Leishmania Skin) , in air higher to observe typically in the nose (Leishmania Mucocutanea), presents severe inflammation of the liver and spleen (Leishmania Visceral).